2013
DOI: 10.4236/jct.2013.47133
|View full text |Cite
|
Sign up to set email alerts
|

Persimmon Leaf Flavonols Enhance the Anti-Cancer Effect of Heavy Ion Radiotherapy on Murine Xenograft Tumors

Abstract: The cell cycle checkpoint system play a pivotal role in the cellular DNA damage response, and the discovery of checkpoint inhibitors is expected to sensitize current cancer therapies. Checkpoint signaling cascades are critically modulated by ATM (ataxia telangiectasia-mutated) and its related molecules. Generally, ATM primarily responds to ionizing irradiation-induced DNA double-strand breaks. Heavy ions from an accelerated carbon ion beam have been used to cure cancer because they are more effective than ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Persimmon (Diospyros kaki L.) leaves, an Asian traditional medicine agent, containing mainly flavonoids, have been also described for their beneficial pharmacological effects including antitumor [80], hypoglycemic [81], antioxidant [82], and anti-inflammatory [82]. Li Chen et al [83] identified four main flavone and flavonol glycosides, rutin (18), quercetin (16), kaempferol (14), and myricetin ( 19), described to have anticancer effect to leukemia, colorectal cancer, neuroblastoma, melanotic melanoma [84], and human prostate cancer cell line [85].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Persimmon (Diospyros kaki L.) leaves, an Asian traditional medicine agent, containing mainly flavonoids, have been also described for their beneficial pharmacological effects including antitumor [80], hypoglycemic [81], antioxidant [82], and anti-inflammatory [82]. Li Chen et al [83] identified four main flavone and flavonol glycosides, rutin (18), quercetin (16), kaempferol (14), and myricetin ( 19), described to have anticancer effect to leukemia, colorectal cancer, neuroblastoma, melanotic melanoma [84], and human prostate cancer cell line [85].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The main constituents found in persimmon leaves include flavonoids, terpenoids, naphthoquinones, coumarins, tannins, sterols, organic acids, fatty acids, and volatile oil 8 . The reported beneficial pharmacological effects of persimmon leaves include antitumor 9 , hypoglycemic 10 , antioxidant 11 , anti-inflammatory 12 , anti-bacterial 13 , antihypertensive 14 , anti-hyperlipidemia 15 , and cardiovascular protective 16 activities. Our previous studies indicated that the ethyl acetate extract of persimmon leaves (2 g/kg) possessed antitumor activity against H 22 hepatoma and S 180 Sarcoma with a tumor inhibition rate of 50.5% and 38.2%, respectively 17 .…”
Section: Introductionmentioning
confidence: 99%
“…As flavonoids are the main bioactive constituents in the ethyl acetate extract of persimmon leaves, we hypothesize that the total flavonoids extract from the persimmon leaves may contribute to the antitumor and immunomodulatory activities of the ethyl acetate extract from the persimmon leaves. Recent studies reported in vitro proliferative and in vivo antitumor activities of flavonoids extracted from persimmon leaves against lung and prostate cancers 9 , 18 . As to our knowledge, there is no report on the cancer immunomodulation effect of total flavonoids extract of persimmon leaves (PLF) and there is no report of its efficacy against liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it significantly increased the cytotoxicity triggered by heavy ion irradiation in A549 adenocarcinoma cells. Pretreatment with persimmon leaf flavonol significantly restrained the decrease of mitotic cells in heavy ion‐exposed cells and reduced tumor mass volume, although it solely did not reveal any effect (Kawakami et al, 2013). On the contrary, in a more recent study, it has been reported that persimmon leaf flavonol exhibited antiproliferative action and induce apoptosis in PC‐3 cells by the activation of oxidative stress and mitochondrial‐related apoptosis (Ding et al, 2017).…”
Section: Pharmacological Actions Of Dsmentioning
confidence: 99%